Synthesis of bovine serum albumin capped boron-doped carbon dots for sensitive and selective detection of Pb(II) ion - Vinayak Sahu; Fahmida Khan (Heliyon, 2020)
Carbon dots have tremendous potential to be used for biochemical sensing and environmental testing due to its superior optical properties and excellent biocompatibility. The surface of carbon dots can be easily functionalized. In the present study boron doped carbon dots have been synthesized using one pot approach by microwave treatment method. The surface of boron doped carbon dots is capped with bovine serum albumin. The maximum fluorescence emission observed at 444 nm when excited upon 345 nm of wavelength. In the normal light, it is light green in colour but when exposed in long wavelength UV light it exhibited blue fluorescence. The carbon dots have an irregular shape with a diameter below 5 nm. The applicability of synthesized carbon dots as the fluorescent sensor has been checked using different metal ions. It is observed that Pb(II) ion shows appreciable and selective quenching. Linear relationship is exist between the decrease in fluorescence intensity and the concentrations of Pb(II) ion in the range from 1 ppb to 10 ppb concentration. Limit of detection is found to be 0.08 ppb. This study will be helpful in the development of new fluorescent nano-biosensors.